ASMAUL HUSNA: LINGUISTIC FORMS, THEOLOGICAL MEANINGS, PEDAGOGICAL IMPLICATIONS, AND THEIR EQUIVALENTS IN INDONESIAN TRANSLATION - Nurul Murtadho (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Viewed from their linguistic forms, Asmaul Husna are classified into the mubalaghah group whose meanings require the addition of “Maha” (the All-/Omni- /the Most) and the non-mubalaghah  group, without the word “Maha”. Out of 99, only 69 names come up in the Qur’an with different frequencies, ranging from 1 to 138 times. The implication of this fact for professional educators is the requirement for pedagogical competence, personality competence, and social competence. Out of 5 data sources, there are 4 variants of translation, and a shift of form and meaning has been found. However, according Islamic theology, all names in Asmaul Husna must  be  translated  with  the  word  “Maha”,  which  shows  perfection  in  divine attributes.    Further research should be directed toward the study of Asmaul Husna in the Hadeeth of the Prophet.